Are Birds Free From the Chains of the Skyway? Balancing Freedom, Responsibility and Reflexivity Disability Service Provision - Gordon, Beth (Disability Studies Quarterly, 2002)
Using personal experience narrative, I will discuss the role of disabled disability service providers as agents in an emancipatory process. Reflexivity is required in order for disabled disability service providers to be effective change agents on behalf of other disabled people without falling into the trap of imposing their own theoretical paradigm or personal agenda onto their disabled service consumers. Ah, my friends from the prison, they ask unto me, "How good, how good does it feel to be free?" And I answer them most mysteriously, "Are birds free from the chains of the skyway?" Bob Dylan